Exploring The Rationality of Religious-Rational Islamic Thinkers Towards The Compatibility of The Islamic Education System - Karim, Abdul Rahim; Hasanuddin, Muhammad Irfan; Fuad, Ah. Zakki; Arifuddin, Arifuddin; Abu Bakar, M. Yunus; Muhaemin, Muhaemin (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
Islamic education is often perceived as less relevant to contemporary demands due to its textual and normative approach. This research seeks to explore the rational perspectives of religious-rational Islamic thinkers regarding the compatibility of the Islamic education system in the 21st century, focusing on the scholars classified by Jawwad Ridla; Ikhwan Al-Shafa', Al-Farabi, Ibn Miskawaih, and Ibn Sina. Each thinker will be examined for their contributions to the Islamic education paradigm. This literature review aims to trace manuscripts, articles, and books related to the rationality of these thinkers and their views on the Islamic education system in the 21st century. The findings reveal the religious-rational epistemology of Islamic education and the perspectives of these thinkers on the compatibility of the Islamic education system with 21st-century needs. These four religious-rational Islamic thinkers collectively provide comprehensive insights into an Islamic education system that can be deemed appropriate for the current century. The implications of this research could enrich the discourse on modern Islamic thought by bridging traditional religious views with rational, modern approaches, thereby identifying Islamic universal values that remain relevant, applicable, and competitive in addressing the challenges of the 21st century and supporting the evolution of Islamic thought amidst contemporary dynamics.